Decreased Heart Rate Variability in HIV Positive Patients Receiving Antiretroviral Therapy: Importance of Blood Glucose and Cholesterol - Askgaard, Gro; Kristoffersen, Ulrik Sloth; Mehlsen, Jesper; Kronborg, Gitte; Kjaer, Andreas; Lebech, Anne-Mette (PloS one, 2011)
The presence of autonomic dysfunction in HIV patients is largely unknown. Early studies found autonomic dysfunction in patients with AIDS. Antiretroviral combination therapy (ART) has dramatically changed the course of the disease and improved prognosis and decreased morbidity. To evaluate whether autonomic dysfunction is present in an ART treated HIV population and if so to identify factors of importance. HIV patients receiving ART for at least 12 months (n = 97) and an age-matched control group of healthy volunteers (n = 52) were included. All were non-diabetic and had never received medication for hypertension. Following a 10 min resting period a 15 min ECG recording was performed. Heart-rate variability (HRV) analysis was performed in accordance with current guidelines and data reported as mean [interquartile range]. Mean normal-to-normal (NN) and total HRV measured as standard deviation of normal-to-normal (SDNN) was lower in HIV patients compared to controls (905 vs. 982 ms; p<0.001 and 48 vs. 54 ms; p = 0.028, respectively). No differences were found between the groups in parasympathetic activity measured as square root of the mean squared difference of successive NN-intervals (RMSSD) or the percent of differences between adjacent NN intervals greater than 50 ms (pNN50). In the HIV positives, haemoglobin A1c correlated inversely with SDNN, RMSSD and pNN50 (p<0.05). Total cholesterol and LDL-C correlated inversely with RMSSD and pNN50 (p<0.05). Neither HIV duration, HIV-RNA, CD4 cell count nor CD4 nadir correlated with time or phase domain HRV variables. Moderate autonomic dysfunction is present in HIV positives patients even with suppressed viral load due to ART. The dysfunction is correlated with HbA1c and hypercholesterolemia but not to duration of HIV or whether the patients were receiving protease inhibitors as part of the ART regime.